Maia. Identificação de uma Cidade. BM99, Bienal da Maia - Carlos Maia (2009)
The relationship between society and the city, can not reduce the spontaneous emergence of urban forms, but the existence of social actors carrying from perspectives of representations and forms of action within the city of Maia. The diversity and complexity of forms of appropriation by the population, its public and semi-public spaces and institutions and are determined by many different factors, both internal order of the urban structure itself or of external nature. They can be a factor of social and urban cohesion or, on the other hand, to emphasize situations of marginality, can be enriching intergenerational relationships and intergroup relationships or, in opposition, only accentuate conflicts, may contribute to the consolidation of local identities and strong or weak repositories of identities. This report seeks to represent the image of the city of Maia by a multidisciplinary look focus on the sociology, the geography and the architecture.